Discrete early maladaptive schema subgroups in remitted bipolar disorders: association with neuropsychological performance, residual symptoms, and psychosocial functioning - M’Bailara, Katia; Munuera, Caroline; Weil, François; Passerieux, Christine; Roux, Paul (Frontiers in Psychology, 2025)
ObjectivesTo better understand the disability and heterogeneity in terms of residual symptoms and psychosocial and cognitive functioning in bipolar disorders (BD), individual discrepancies in the activation of early maladaptive schemas (EMS) are relevant to investigate. This study aimed to identify activation profiles of EMS and to investigate the association between identified profiles and disability during euthymia.DesignThis is a cross-sectional study.MethodsClinical data, psychosocial functioning, neuropsychological performance and EMS were collected in euthymic outpatients with a BD. Clustering was performed on EMS activation, followed by inter-cluster comparisons on variables above using post-hoc tests. A multivariate regression was used to confirm associations between clusters and variables of interest by controlling for covariates.ResultsThanks to a person-oriented approach, our results showed three profiles of EMS: “Hypoactivation,” “Light activation.” and “Major Hyperactivation.” Individuals in the light and major hyper activated clusters had worse psychosocial functioning compared to individuals in the hypoactivated cluster. There were no differences in neuropsychological performance between the different profiles of EMS, thus suggesting the independence of these sources of variance in psychosocial functioning of individuals with BD.ConclusionThis paper highlights the importance of considering individual personality and functioning to better understand the heterogeneity in BD during euthymia. For some people, schema therapy seems particularly relevant due to the overactivation of EMS, and even more so because these people have particularly marked functional impairments and clinical severity.